Age Effects in Second Language Learning: Stepping Stones Toward Better Understanding. (13th February 2013) - DeKeyser, Robert M.
Abstract : The effect of age of acquisition on ultimate attainment in second language learning has been a controversial topic for years. After providing a very brief overview of the ideas that are at the core of the controversy, I discuss the two main reasons why these issues are so controversial: conceptual misunderstandings and methodological difficulties. The main part of the article then makes suggestions for improvement in subject selection, data collection, and instrumentation, in the hope that both sides of the debate will be able to agree on them. More sophisticated research in this area is of the utmost importance given how crucial understanding age effects is for educational policy and curriculum design. Where foreign language learning rather than second language learning is concerned, directly relevant research, carried out with classroom foreign language learners, is even more sorely needed.